MEMBANGUN PEREKONOMIAN MASYARAKAT MELALUI USAHA TANI SAYURAN ORGANIK DI MASA PANDEMI - Fadillah Nuraini; Nur Azizah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
The decline in the community's economy is part of the impact of the Covid-19 pandemic that has been going on since the beginning of 2020. This has led to an increase in the level of poverty and unemployment in Indonesia. This study aims to describe building the community's economy through organic vegetable farming during the pandemic by PKK in Karanglewas Kidul Village, Banyumas Regency, Central Java. This research was conducted using qualitative research methods where the data collection techniques were observation and interviews with the subjects of PKK women in Karanglewas Kidul Village. The results are: Organic vegetable cultivation is carried out as an effort to get used to living a healthy life and eating healthy food, and can provide real benefits for the community in the form of additional income as a form of community economic development, besides that the community can also develop independently through the use of home yard land as a place to live. organic vegetable cultivation.